Ser-653-Asn substitution in the acetohydroxyacid synthase gene confers resistance in weedy rice to imidazolinone herbicides in Malaysia - Ruzmi, Rabiatuladawiyah; Ahmad Hamdani, Muhammad Saiful; Mazlan, Norida (Public Library of Science, 2020)
The continuous and sole dependence on imidazolinone (IMI) herbicides for weedy rice control has led to the evolution of herbicide resistance in weedy rice populations across various countries growing IMI herbicide-resistant rice (IMI-rice), including Malaysia. A comprehensive study was conducted to elucidate occurrence, level, and mechanisms endowing resistance to IMI herbicides in putative resistant (R) weedy rice populations collected from three local Malaysian IMI-rice fields. Seed bioassay and whole-plant dose-response experiments were conducted using commercial IMI herbicides. Based on the resistance index (RI) quantification in both experiments, the cross-resistance pattern of R and susceptible (S) weedy rice populations and control rice varieties (IMI-rice variety MR220CL2 and non-IMI-rice variety MR219) to imazapic and imazapyr was determined. A molecular investigation was carried out by comparing the acetohydroxyacid synthase (AHAS) gene sequences of the R and S populations and the MR220CL2 and MR219 varieties. The AHAS gene sequences of R weedy rice were identical to those of MR220CL2, exhibiting a Ser-653-Asn substitution, which was absent in MR219 and S plants. In vitro assays were conducted using analytical grade IMI herbicides of imazapic (99.3%) and imazapyr (99.6%) at seven different concentrations. The results demonstrated that the AHAS enzyme extracted from the R populations and MR220CL2 was less sensitive to IMI herbicides than that from S and MR219, further supporting that IMI herbicide resistance was conferred by target-site mutation. In conclusion, IMI resistance in the selected populations of Malaysian weedy rice could be attributed to a Ser-653-Asn mutation that reduced the sensitivity of the target site to IMI herbicides. To our knowledge, this study is the first to show the resistance mechanism in weedy rice from Malaysian rice fields.